PERANCANGAN INFOGRAFIK UNTUK ORGANISASI YAYASAN KASIH ANAK KANKER INDONESIA - Grace Theresa Angelina Goein (Jurnal Vicidi, 2020)
Child cancer is a disease that has the highest mortality rate in Indonesia. In addition, cancer is a complex disease caused by the growth of cells that are not normal. This cancer grows or develops quickly, cannot be controlled, and always spreads through the blood tissues and attacks the organs in the body in an important part and can also arise in the bone nerves in the back. As a result of the many parents who are less able to pay for treatment to their children who suffer from cancer, therefore, YKAKI was made. YKAKI is a non-profit organization and is an organization to help provide assistance in the form of treatment in hospitals, as well as getting facilities one of which is activities such as other children but is made specifically for children who suffer from cancer. YKAKI is based in Jakarta but has many branches, one of which is in Surabaya. However, the existence of YKAKI in the Surabaya area is less well known by the people of Surabaya due to the lack of care and assistance from the surrounding community. Therefore, in this article contains information in the form of infographics related to funding or donations so that people have concern and are encouraged to help the Indonesian Cancer Child Love Foundation (YKAKI) in the Surabaya area, East Java. Keywords: Child cancer, infographics, public awareness, articles.